Elementary Swahili Lugha na Utamaduni - Mwangi, Peter (Open textbook library., 2023)
Elementary Swahili: Lugha na Utamaduni is intended for both heritage and non-heritage elementary Swahili learners. It introduces the learners to aspects of Standard Swahili language and culture with the view of enhancing their intercultural competence in Swahili. The topics are well-integrated to enable the learners to easily apply what they learn in each topic into their daily interactions in Swahili about themselves, family, friends, immediate world, and East Africa. Thus, at the end of Elementary Swahili, learners should be able to carry out basic conversations in Swahili about themselves, their world, and East Africa. Further, the coursebook will incorporate common Swahili cultural practices in all the topics with the view of enhancing the learners’ intercultural competence.